Syirik Dalam Era Digital: Tantangan dan Transformasi Praktik Spiritual Dikalangan Remaja - Alya Dwi Rahayu; Anabel Nadea Pasha; Prameswari Prameswari; Sri Natalia Sari (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The digital era has changed the way teenagers interact with information and spiritual practices. On the one hand, quick access to various sources can enrich religious knowledge. On the other hand, inaccurate or deviant information is also easily spread, potentially leading to shirk practices. Teenagers in the identity search phase are often influenced by social media content and popular culture that can cloud their understanding of monotheism. The main challenge faced is the shift in spiritual values where traditional religious practices are often replaced by new rituals and beliefs that are not in accordance with religious teachings. The transformation of spiritual practices among teenagers is also seen in their adaptation to digital platforms, where many seek community and spiritual support online. The purpose of this study is to identify effective strategies to support a correct understanding of monotheism and reduce the influence of shirk, as well as to utilize the potential of digital media for constructive religious education. Empowering teenagers in understanding and practicing religious teachings critically is very important to maintain the authenticity of spiritual practices in the digital era. The method used in this study is a descriptive qualitative method, by making the Qur'an, books of hadith, books, magazines, articles and related journals as the main reading sources. The results of the study show; (1) that the advancement of digital technology has a great influence on the imitation of foreign cultures that smack of polytheism, (2) several figures exemplify the culture of polytheism while social media spreads it, (3) It is difficult to stem the flood of information on social media. Efforts to improve it include frequently listening to studies and attending training on the dangers of polytheism.